Investigation of the Effect of Layer Thickness and Raster Angle Orientation on the Bending Properties of Additive Manufactured Polylactic Acid (PLA) Polymer - Orhorhoro, Ejiroghene Kelly; Sadiq, Sule; Igbagbon, Efe Justic; Omoyi, Cordelia Ochuole (Journal of Advanced Mechanical Engineering Applications, 2025)
Today’s mechanical engineering applications of 3D printing are highly beneficial for the study and creation of a wide range of components, from simple everyday structures to intricate ones. In fused deposition modeling, a component is usually created by applying the concepts of layer-by-layer material deposition and rapid prototyping. The effect of layer thickness and raster angle orientation on the bending characteristics of PLA beam samples that were 3D printed was examined in this work. A stereolithography (STL) file format, which was produced using modeling software (CAD), is used to transmit data into the machine’s software. Three distinct raster angle orientations—0°, 45°, and 90°—as well as layer thicknesses of 0.155 mm, 0.255 mm, and 0.355 mm and 100% infill were used to print the PLA beam samples. The Instron machine was used to perform a 3-point test in order to ascertain the PLA beam samples’ bending characteristics. The PLA beam sample’s size and geometry were modeled using the ASTM D790-10 standard procedure. The study’s findings indicate that the bending characteristics of the PLA beam samples are influenced by the layer thickness and raster angle orientation. In contrast to 45° and 90° raster angle orientation, it was found that 0° had the greatest bending effect. Additionally, in all evaluated PLA beam samples, a layer thickness of 0.355 mm yielded superior results than a layer thickness of 0.155 mm. Therefore, a raster angle of 0° and a layer thickness of 0.355 mm should be utilized when bending stress is taken into account for 3D printing PLA materials.